JobStart Part 2 The Right Job–Just for You - Elizabeth B. Bolton; George O. Hack (EDIS)
This document is FY346, Part 2 of an 8 part series developed for the Department of Family, Youth and Community Sciences, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised version prepared for electronic publication November 2001 by Elizabeth B. Bolton, professor. Original version prepared for publication May 1997 by Elizabeth B. Bolton and George O. Hack.